2022
DOI: 10.30880/ijscet.2022.13.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Soil Strength and Microstructure of Palm Oil Boiler Ash with Sodium Hydroxide and Sodium Silicate as Alkaline Solution

Abstract: Palm oil boiler ash is a type of industrial waste from palm oil production, which abundantly disposed on landfill, and contaminate the soil and environment. Recently, boiler ash as a by-product is introduced as an additive in chemical stabilization, known as geopolymer. An alkaline solution functions to activate the silica-alumina structure bonding to replace the Ordinary Portland Cement in concrete application but few in soil stabilization study. This study investigates the strength of laterite with a geopoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Meanwhile, the use of POFA-based geopolymers has also been studied by Malaysian researchers in recent years, but these studies focused on the stabilisation of silt and clay soils. For example, Zainuddin et al [43] produced POFA geopolymers to stabilise very silty soil, while Abdeldjouad et al [44] focused on the improvement of residual soil and marine clay using POFA geopolymers, and lastly, [45] conducted a study on the use of POFA geopolymers to enhance the shear strength of silts and clays. The studies carried out by Yusof [42] and Zainuddin et al [43] showed promising results, with stabilised soil UCS ranging from 900-4180 kPa.…”
Section: Research Gap In Malaysiamentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the use of POFA-based geopolymers has also been studied by Malaysian researchers in recent years, but these studies focused on the stabilisation of silt and clay soils. For example, Zainuddin et al [43] produced POFA geopolymers to stabilise very silty soil, while Abdeldjouad et al [44] focused on the improvement of residual soil and marine clay using POFA geopolymers, and lastly, [45] conducted a study on the use of POFA geopolymers to enhance the shear strength of silts and clays. The studies carried out by Yusof [42] and Zainuddin et al [43] showed promising results, with stabilised soil UCS ranging from 900-4180 kPa.…”
Section: Research Gap In Malaysiamentioning
confidence: 99%
“…For example, Zainuddin et al [43] produced POFA geopolymers to stabilise very silty soil, while Abdeldjouad et al [44] focused on the improvement of residual soil and marine clay using POFA geopolymers, and lastly, [45] conducted a study on the use of POFA geopolymers to enhance the shear strength of silts and clays. The studies carried out by Yusof [42] and Zainuddin et al [43] showed promising results, with stabilised soil UCS ranging from 900-4180 kPa. At the time of writing, there are no known studies conducted on the improvement of tropical peat soils with POFA-based geopolymers.…”
Section: Research Gap In Malaysiamentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the use of agricultural and industrial waste-derived geopolymer materials as soil stabilizers has been applied in the geotechnical field, with published studies reporting on the enhancement of engineering properties and improved durability of weak soils [6,7]. Various types of geopolymer source materials were used for soil stabilization purposes, such as coffee grounds [8], tea wastes [9], fly ash [10,11], GGBFS [6,12], and POFA [13][14][15]. In the context of this study, the outcomes of selected studies conducted on POFA-based geopolymers used as construction and weak soil stabilizer materials are discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the existing studies on the use of POFA-based geopolymer materials are very limited, and the outcome of these studies has been discussed in depth in a recent review paper [18]. In the study conducted by Zainuddin et al [15], POFA geopolymer was used as a soil stabilizer for weak laterite soil. They reported that the strength of laterite soil improved from 106 kPa to 340 kPa after 7 days of curing, with a 15% POFA geopolymer content.…”
Section: Introductionmentioning
confidence: 99%